Knowledge and attitude toward health and CVD risk factors among firefighters in Cape Town, South Africa - Jaron Ras; Duncan Mosie; Matthew Strauss; Lloyd Leach (SAGE Publishing, 2021)
Background: Firefighting is a hazardous occupation, and the firefighters' fitness for duty is affected by their knowledge of and attitudes toward their health and their relationship in the development of cardiovascular disease (CVD). The aim of this study was to assess knowledge and attitude toward health and CVD risk factors among firefighters in South Africa. Design and Methods: The study used a cross-sectional research design. A sample of 110 firefighters, males and females, aged 18 to 65 years were conveniently sampled from the City of Cape Town Fire and Rescue Service. A researcher-generated self-administered questionnaire was completed online to obtain data from firefighters. A p-value of less than 0.05 indicated statistical significance. Results: The results showed that 52.8% of firefighters had a poor knowledge of health, and 47.2% had a good knowledge of health, while 10% reported a negative attitude towards health and 90.0% had a positive attitude towards health. There was a significant difference between firefighters' knowledge of health and their attitudes toward health (p<0.05), particularly related to marital status, age, years of experience and in those with CVD risk factors (p<0.05). Significant correlations were found between knowledge of CVD and knowledge of health-risk behaviors (p<0.05). Conclusion: Significant differences in health knowledge and attitudes toward health were present in married, aged and hypertensive firefighters. Overall health knowledge and health-risk behaviours were significant predictors of attitudes toward health.